Purine derivatives excretion function in relation to the fiber/protein ratio in the diet of alpacas (Vicugna pacos) - Rúa M., Viviana (2017)
The aim of this study was to evaluate the relationship of the neutral detergent fibre/ crude protein on urinary excretion of purine derivatives (PD) in alpacas. The experimental design was a 3x3 Latin Square. Three male Huacaya alpacas, 2.5 years old, confined in individual pens were used. Feed was provided once daily and water ad libitum. Three treatments based on oat hay were used where the ratios of fibre/protein was obtained according to the proportions of stems and leaves. The treatments were: T1, leaves oat hay, 58.24% neutral detergent fiber (NDF) and 6.80% crude protein (CP); T2, leaves and stems of oats, 66.31% FDN and 6.36% PC; T3, stems of oats, 70.22% FDN and 5.75% PC. Each experimental period lasted 14 days, 10 days of adaptation and 4 days of evaluation. The levels of DP urine were analyzed by High Performance Liquid Chromatography (HPLC). The total daily excretion of DP was 25.51 (T1), 28.07 (T2) and 14.21 (T3) mg/d. The daily excretion of allantoin, hypoxanthine, xanthine and the total excretion of DP were similar among treatments. The results showed that the NDF/PC ratio at the levels used does not influence DP excretion in the urine of alpacas.